2009
DOI: 10.1039/b911509a
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic electrospun POSS-PMMA copolymer fibres with highly ordered nanofibrillar and surface structures

Abstract: A POSS-PMMA copolymer has been synthesised by conventional free-radical polymerisation reaction. Uniform electrospun fibres from this copolymer showed a water contact angle as high as 165 degrees with a sliding angle as low as 6 degrees . For the first time, we found that the electrospun fibres had a bundled nanofibril secondary structure with an ordered POSS morphology on the fibre surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 33 publications
0
66
0
Order By: Relevance
“…It can be seen from the table that only webs produced in ref. 82 and to some extent in ref. 64 can be considered as stable and self-cleaning.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen from the table that only webs produced in ref. 82 and to some extent in ref. 64 can be considered as stable and self-cleaning.…”
Section: Reviewmentioning
confidence: 99%
“…Other silicone based polymers were synthesized by Ma et al 64 and Xue et al 82 and only these two papers in this section reported high WCA, low hysteresis and produced mechanically stable webs. Ma et al 64 utilized the low surface tension of polydimethylsiloxane (PDMS), but because this polymer cannot be made into solid fibers, the authors synthesized the PS-PDMS di-block copolymer and electrospun it from a mixture with pure PS in the THF:DMF solution.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Having eight organic groups surrounding a cagelike core connected by Si-O-Si bonds, POSS was highly soluble in many kinds of organic solvents. 19 In this article, we employed a covalent functionalization approach to obtain oil dispersible GO using aminopropylisobutyl polyhedral oligomeric silsesquioxane (POSS-NH 2 ) as modier (Fig.…”
mentioning
confidence: 99%
“…These unique characteristics plus the functionalities from the polymers themselves impart nanofibers with many desirable properties for advanced applications. Several methods have been developed to fabricate nanofibers, such as template (Ikegame et al, 2003), self-assembly (Hong et al, 2003), phase separation (Ma and Zhang, 1999), meltblowing (Ellison et al, 2007) and electrospinning (Doshi and Reneker, 1995, Lin et al, 2004, Lin et al, 2005a, Fang et al, 2007, Xue et al, 2009, Fang et al, 2010. Electrospinning has been regarded as the most promising approach to produce continuous nanofibers on a large scale and the fiber diameter can be adjusted from nanometers to micrometers (Li and Xia, 2004b).…”
Section: Introductionmentioning
confidence: 99%